Association Between Neutrophil Percentage to-Albumin Ratio, Neutrophil to-Lymphocyte Ratio, Platelet-to Lymphocyte Ratio and in-Hospital Mortality in Elder Patients with Bloodstream Infections - Yu Z; Liu C; Gong M; Zhang P; Pei C; Liu X; Han X; Zhu P; Xu G; Du Y (Journal of Inflammation Research)
Zhenghao Yu,1,2,* Chuanbin Liu,1,* Meiliang Gong,3,* Pinzheng Zhang,4 Changbai Pei,1 Xinran Liu,2 Xinjie Han,2 Pingjun Zhu,5 Guogang Xu,1 Yingzhen Du4 1Health Management Institute, The Second Medical Center and National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, People’s Republic of China; 2Medical School of Chinese PLA, Beijing, People’s Republic of China; 3Department of Laboratory Medicine, Second Medical Center, Chinese PLA General Hospital, Beijing, People’s Republic of China; 4Department of Disease Control and Prevention, The Second Medical Center & National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, People’s Republic of China; 5Department of Respiratory and Critical Care Medicine, The Second Medical Center and National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guogang Xu, Email gxu@301hospital.org Yingzhen Du, Email zhenzhen52@163.comBackground: Bloodstream infections (BSI) is one of the major complications in elder inpatients, which is closely related to inflammation. Neutrophil percentage-to-albumin ratio (NPAR), Neutrophil-to-lymphocyte ratio (NLR), and Platelet-to-lymphocyte (PLR) are convenient predictors of inflammation and poor prognosis for a wide range of diseases. However, the association of NPAR, NLR and PLR with in-hospital mortality in elder inpatients with BSI are unclear. This study aimed to investigate the association and the predictive value of NPAR, NLR and PLR with in-hospital mortality.Methods: This study included older patients with BSI who were hospitalized in a large healthcare center in Beijing from December 2011 to January 2024. Kaplan-Meier curves and Cox regression analysis were used to explore the association of NPAR, NLR and PLR with in-hospital mortality. Restricted cubic spline analysis and Receiver operating characteristics (ROC) were performed to access the dose-response relationship and predictive value of NPAR, NLR and PLR with in-hospital mortality, respectively.Results: A total of 511 older patients with BSI were included in this study, with a mean age of 89.9± 8.5 years, of which 85 deaths occurred during hospitalization (16.6%). After adjustment, the continuous NPAR level was associated with increased risk of in-hospital mortality (hazard ratio [HR] = 1.08, 95% confidence interval [CI]: 1.05, 1.12). The third tertile group of NPAR significantly increased the risk of in-hospital mortality compared to the first tertile group of NPAR (HR = 3.36, 95% CI: 1.87, 6.02). However, no association between NLR, PLR and in-hospital mortality was found. The area under the ROC curve of NPAR, NLR, and PLR for predicting mortality were 0.681 (95% CI: 0.615– 0.747), 0.666 (95% CI: 0.598– 0.733), and 0.510 (95% CI: 0.420– 0.559), respectively.Conclusion: Elevated NPAR was associated with higher risk of in-hospital mortality in older patients with BSI. NPAR may serve as a convenient and simple prognostic indicator.Keywords: biomarkers, neutrophil percentage-to-albumin ratio, neutrophil-to-lymphocyte ratio, platelet-tolymphocyte, bloodstream infections, elder, mortality